Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To determine the equation of the line that is parallel to the given line passing through the points [tex]\((0, -3)\)[/tex] and [tex]\((2, 3)\)[/tex] and that also passes through the point [tex]\((-1, -1)\)[/tex], we can proceed step-by-step as follows:
Step 1: Calculate the slope of the given line.
Given points:
- [tex]\((x_1, y_1) = (0, -3)\)[/tex]
- [tex]\((x_2, y_2) = (2, 3)\)[/tex]
The formula to calculate the slope ([tex]\(m\)[/tex]) between two points is:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Substituting the given points:
[tex]\[ m = \frac{3 - (-3)}{2 - 0} = \frac{3 + 3}{2} = \frac{6}{2} = 3 \][/tex]
So, the slope of the given line is [tex]\(m = 3\)[/tex].
Step 2: Determine the equation of the line parallel to the given line.
A line parallel to another line will have the same slope. Therefore, the slope of our new line must also be [tex]\(3\)[/tex].
Step 3: Use the point-slope form of the equation of a line.
The point-slope form of a line's equation is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Here, our slope [tex]\(m = 3\)[/tex] and our point is [tex]\((-1, -1)\)[/tex].
Substituting the point [tex]\((-1, -1)\)[/tex] into the point-slope form:
[tex]\[ y - (-1) = 3(x - (-1)) \][/tex]
Simplifying, we get:
[tex]\[ y + 1 = 3(x + 1) \][/tex]
Conclusion:
The equation of the line parallel to the given line passing through the point [tex]\((-1, -1)\)[/tex] is:
[tex]\[ y + 1 = 3(x + 1) \][/tex]
Thus, among the given options, the correct one is:
[tex]\[ y + 1 = 3(x + 1) \][/tex]
Step 1: Calculate the slope of the given line.
Given points:
- [tex]\((x_1, y_1) = (0, -3)\)[/tex]
- [tex]\((x_2, y_2) = (2, 3)\)[/tex]
The formula to calculate the slope ([tex]\(m\)[/tex]) between two points is:
[tex]\[ m = \frac{y_2 - y_1}{x_2 - x_1} \][/tex]
Substituting the given points:
[tex]\[ m = \frac{3 - (-3)}{2 - 0} = \frac{3 + 3}{2} = \frac{6}{2} = 3 \][/tex]
So, the slope of the given line is [tex]\(m = 3\)[/tex].
Step 2: Determine the equation of the line parallel to the given line.
A line parallel to another line will have the same slope. Therefore, the slope of our new line must also be [tex]\(3\)[/tex].
Step 3: Use the point-slope form of the equation of a line.
The point-slope form of a line's equation is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Here, our slope [tex]\(m = 3\)[/tex] and our point is [tex]\((-1, -1)\)[/tex].
Substituting the point [tex]\((-1, -1)\)[/tex] into the point-slope form:
[tex]\[ y - (-1) = 3(x - (-1)) \][/tex]
Simplifying, we get:
[tex]\[ y + 1 = 3(x + 1) \][/tex]
Conclusion:
The equation of the line parallel to the given line passing through the point [tex]\((-1, -1)\)[/tex] is:
[tex]\[ y + 1 = 3(x + 1) \][/tex]
Thus, among the given options, the correct one is:
[tex]\[ y + 1 = 3(x + 1) \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.